Earth System Science : A Very Short Introduction - Lenton, Tim (Oxford Oxford University Press, 2016)
Earth System Science regards the Earth as an integrated system of interacting atmosphere, oceans, rocks, and biosphere. In this Very Short Introduction, Tim Lenton explores its development over 4.6 billion years, its present state, and its future.
Include Illustrations, References and Index.
A Very Short Introduction.
Keywords: Earth sciences -- Sciences - Earth